Medicinal Herbal Recommendation for Irritable Bowel Syndrome in Medieval Persian Medicine - Farshad AMINI-BEHBAHANI; Mohsen BAHRAMI; Behzad EFTEKHAR; Bagher MINAEI; Majid DADMEHR (Tehran University of Medical Sciences, 2019)
No abstract No abstract No abstract